Addressing the dual health epidemics of HIV and sexual abuse among children and adolescents in Kenya: uptake of HIV counseling and post-exposure prophylaxis - Ajema C; Mbugua C; Memiah P; Wood C; Cook C; Kotut R; Digolo L (Dove Medical Press, 2017)
Carolyne Ajema,1 Charity Mbugua,2 Peter Memiah,3 Camille Wood,3 Courtney Cook,4 Ronald Kotut,2 Lina Digolo1 1Research and Strategic Information Department, LVCT Health, Nairobi, Kenya; 2Post Rape Care Department, LVCT Health, Nairobi, Kenya; 3Department of Public Health, University of West Florida, University Parkway, Pensacola, FL, USA; 4Biology Department, University of West Florida, University Parkway, Pensacola, FL, USA Purpose: Child sexual abuse and HIV are key health challenges in Kenya. In 2015, LVCT Health conducted a study aimed at assessing the quality of HIV-related services offered to child survivors of sexual violence in public health facilities.Materials and methods: A qualitative data collection approach was utilized. Qualitative data were collected through in-depth interviews with 31 providers. Quantitative methods included a retrospective review of 164 records of child survivors of rape who had accessed services 6 months prior to the commencement of the study. SPSS Version 22 was used in the descriptive analysis of the medical records. Client exit interviews and observation data were analyzed using MS Excel. In-depth interviews were analyzed using a thematic analytical approach.Results: Twenty-seven percent (n=164) survivors were documented to have received the first dose of postexposure prophylaxis (PEP). Providers did not conduct HIV pre- and posttest counseling for the survivors. There were no longitudinal follow-up mechanisms to ensure child survivors initiated on PEP adhered to the treatment plan. Less than 30% of survivors returned to the facility for PEP adherence counseling and follow-up HIV testing. Twenty providers cited capacity gaps in undertaking HIV risk assessment for child survivors. Limited availability of PEP is a barrier to HIV prevention, as most departments only offer services between 8 am and 5 pm. HIV tests were only available on weekdays before 5 pm. PEP being out of stock remains a barrier to HIV prevention.Conclusion: Existing post-rape care services are not adequately structured to facilitate delivery of quality HIV-related services to child survivors. Health provider capacity in the management of children remains weak due to lack of skill-based training on the dynamics of responding to the needs of child survivors. There is a need for standard operating procedures and training modules on the prevention of HIV in the context of child sexual abuse. Keywords: child sexual abuse, post-rape care, sexual violence, HIV, PEP, children in Kenya